'If I climb a wall of ten meters': capoeira, parkour and the politics of public space among (post)migrant youth in Turin, Italy. (14th March 2016) - De Martini Ugolotti, Nicola; Moyer, Eileen
ABSTRACT: Rather than being seen as citizens, the children of immigrants are portrayed as a population to be controlled and contained across Europe. In Italy today, debates about cultural 'authenticity' and renewed nationalism accompany waves of moral panic that depict a country under siege by illegal and unwanted immigrants. Specifically in cities, immigrants and their children are imagined and portrayed as alien and out of place. Drawing on fourteen months of ethnographic research in Turin, Italy, with children of immigrants aged between 16 and 21, De Martini Ugolotti and Moyer illustrate how these youth make use of their bodies through capoeira and parkour practices to contest and reappropriate public spaces, thereby challenging dominant visions about what constitutes the public, how it should be used and by whom. They analyse the 'body in place' to understand how the children of immigrants navigate unequal spatial relations and challenge dominant regimes of representation, while also attempting to improve their life conditions and reach their personal goals.